Determining the Patient Acceptable Symptomatic State for Patients Undergoing Arthroscopic Partial Meniscectomy in the Knee. Issue 4 (March 2020) - Dwyer, Tim; Zochowski, Thomas; Ogilvie-Harris, Darrell; Theodoropoulos, John; Whelan, Daniel; Chahal, Jaskarndip
Background: Arthroscopic partial meniscectomy is one of the most common procedures in orthopaedic surgery. The patient acceptable symptomatic state (PASS), which defines a level of symptoms above which patients consider themselves well, remains to be well-defined in this population. Purpose: Using an anchor-based approach, our goal was to determine the 1-year PASS for the Knee injury and Osteoarthritis Outcome Score (KOOS), the International Knee Documentation Committee (IKDC) Subjective Knee Form, the Western Ontario Meniscal Evaluation Tool (WOMET), and the Marx Activity Scale (MAS) in patients who were treated with partial knee meniscectomy. Study Design: Case series; Level of evidence, 4. Methods: A consecutive series of patients with knee meniscal tears and a Kellgren-Lawrence grade of 0 to 2 treated with arthroscopic partial meniscectomy were eligible. The KOOS (0-100), IKDC (0-100), WOMET (0-100), and MAS (0-16) were administered at baseline and 12 months postoperatively. An external anchor question at 1 year postoperatively was used to determine PASS values. A receiver operating characteristic curve (ROC) analysis was used to determine the PASS value at which patients considered their status to be satisfactory. Results: The study included 110 patients (mean ± SD age, 53.8 ± 12.0 years), 57.3% were male, and the follow-up rate was 82%. In total, 70% of patients had an Outerbridge arthroscopic grade of 2 or lower. Based on ROC analysis, the 1-year postoperative PASS values (sensitivity, specificity) were 64.3 (47.8, 100.0) for KOOS Symptoms, 81.6 (71.6, 100.0) for KOOS Pain, 82.4 (82.1, 86.4) for KOOS Function in Daily Living, 71.0 (62.7, 81.8) for KOOS Function in Sport and Recreation, 51.0 (83.6, 95.5) for KOOS Knee-Related Quality of Life, 56.2 (82.1, 100.0) for IKDC, 58.5 (79.1, 100.0) for WOMET, and 7.0 (44.8, 68.2) for MAS. Baseline scores did not affect the PASS threshold across the different instruments. However, patients with higher baseline scores were more likely to achieve the PASS for the KOOS Symptoms (odds ratio [OR], 2.808; P = .047), IKDC (OR, 4.735; P = .006), and WOMET (OR, 2.985; P = .036). Age, sex, and cartilage status were not significantly related to the odds of achieving the PASS for any of the patient-reported outcome measures. Conclusion: These findings allow researchers and clinicians to determine whether partial meniscectomy is meaningful to patients at the individual level and will be helpful for responder analysis in future trials related to the treatment of meniscal abnormality.